Consumer Behavior In Online Purchase of Seeds and Ornamental Plants - Durrotun Nafisah; Mardiyah Hayati (Universitas Muhammadiyah Jakarta, 2022)
The covid-19 pandemic has forced most people of Indonesia to do their activities from home, one of which is shopping which is also carried out online. Some people in Indonesia prefer to buy seeds and ornamental plants online even though these products are vulnerable to damage due to the limited durability and expiration date. The purpose of this study is to identify whether there is an influence of comsumer behavior on online purchasing decisions for seeds and ornamental plants in Indonesia. The analysis techniques used are validity test, reliability test, and multiple linear regression. The results showed that lifestyle does not affect purchasing decisions, while trust, convenience, and web quality affect purchasing decisions. The results of the F-test suggested that the variables of lifestyle, trust, convenience, and web quality, simultaneously influence the decision to purchase seeds and ornamental plants online.